2007
DOI: 10.1027/1614-2241.3.4.139
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing, Summarizing, and Comparing Odds Ratio Structures

Abstract: The odds ratio is one of the main measures of association in 2 × 2 tables. For larger tables, summary measures of association have been proposed as well as modeling strategies, where the odds ratios can be deduced from the parameters of a model. We propose a computationally simple scaling methodology, which gives a summary measure of association and a visualization of the odds ratio structure. Different variants of the methodology are discussed and compared, both theoretically and empirically. The methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Odds ratios (OR) were calculated as OR = [( a / b )/( c / d )] for each session as the likelihood that a given posture–vocalization dyad would co‐occur. The OR is a descriptive measure of effect size for categorical variables and a primary measure of association in 2 × 2 frequency tables (Andrade, ; De Rooij & Anderson, ). ORs greater than 1 indicated that contingencies were more likely to occur than not, ORs less than 1 indicate that contingencies were unlikely to occur, and p values indicate whether these likelihoods were significant.…”
Section: Resultsmentioning
confidence: 99%
“…Odds ratios (OR) were calculated as OR = [( a / b )/( c / d )] for each session as the likelihood that a given posture–vocalization dyad would co‐occur. The OR is a descriptive measure of effect size for categorical variables and a primary measure of association in 2 × 2 frequency tables (Andrade, ; De Rooij & Anderson, ). ORs greater than 1 indicated that contingencies were more likely to occur than not, ORs less than 1 indicate that contingencies were unlikely to occur, and p values indicate whether these likelihoods were significant.…”
Section: Resultsmentioning
confidence: 99%
“…The odds ratio (OR) is one of the main measures of association in 2 × 2 contingency tables. The OR is also commonly used to describe the relationship between the row and column variables in I × J two‐way contingency tables, see for example Altham (), Goodman (, ), Greenacre (), De Rooij & Anderson () and de Rooij & Heiser (). In this case the total number of ORs to compute is [ I ( I − 1)]/2 × [ J ( J − 1)]/2 although this number can be reduced using the basic set of ORs, as defined by De Rooij & Anderson ().…”
Section: Introductionmentioning
confidence: 99%
“…The OR is also commonly used to describe the relationship between the row and column variables in I × J two‐way contingency tables, see for example Altham (), Goodman (, ), Greenacre (), De Rooij & Anderson () and de Rooij & Heiser (). In this case the total number of ORs to compute is [ I ( I − 1)]/2 × [ J ( J − 1)]/2 although this number can be reduced using the basic set of ORs, as defined by De Rooij & Anderson (). Irrespective of the results of De Rooij & Anderson (), in this paper we consider the complete set of ORs, because, as we will show, the matrix containing all of the ORs is linked in an important way with the original two‐way contingency table of dimension I × J .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Erosheva 2005) employed a geometric approach to compare the potential value of using the Grade of Membership, latent class, and Rasch models in representing population heterogeneity for 2 J tables. Similarly, (Heiser 2004, De Rooij and Anderson 2007, De Rooij and Heiser 2005 have given geometric characterisations linked to odds ratios and related models for I × J tables, (Greenacre and Hastie 1987) focus on the geometric interpretation of correspondence analysis for contingency tables, (Carlini and Rapallo 2005) described some of the links to (Fienberg and Gilbert 1970) as well as the geometric structure of statistical models for case-control studies, and (Flach 2003) linked the geometry to Receiver Operating Characteristic space.…”
Section: Introductionmentioning
confidence: 99%